Analisa Penerapan Fuzzy Tahani Pada Proses Retrieve Case-Based Reasoning - Feby Meivianni Contessa (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2016)
This research focuses on the application of fuzzy analysis on the process of retrieving tahani case-based reasoning in the search for restaurant. The design of this study using SDLC (System Development Life Cycle). Cases data of search restaurant totaling 50 cases obtained from the distribution of the questionnaire. The data is divided into 40 cases for the base case and 10 cases for testing. The results showed that the respondents thought the suitability of the recommendation given CBR system much as 60% CBRFuzzy and 53% according to the respondents wanted.